Profil of Japan - Stesen Televisyen Malaysia Berhad (Kuala Lumpur : Stesen Televisyen Malaysia Berhad, 1995)
The program about the activities done by Japan in order to protect their fauna from extinct. There have some programs to protect animals such as birds, porcupine and etc
Title from container
Copy available in DVD format
Keywords: Endangered species; Wildlife conservation; Extinct animals